Entrepreneurial competitiveness in the knowledge economy: factors defining the innovativeness of small and medium size enterprises - Τσάμπρα Μαρία; Παλάσκας Θεοδόσιος Β. (SPOUDAI Journal of Economics and Business, 2004)
The present paper is based on state-of-the-art research in European and Asian labour-intensive and technology-intensive industries, concerning the competitiveness of small and medium size enterprises in the context of knowledge-economy. Cross-country and cross-industry econometric analysis of the primary qualitative and quantitative information establishes that firm economic performance depends on technological and innovation capacity. The deviation in the technological capabilities and competitiveness of firms and industrial agglomerations is strongly related to different structural, as well as functional and institutional configurations of business milieux. The identification of the factors determining innovativeness suggests that firm innovative and competitive capacity depend heavily rather on the endogenously developed technology, than on exogenous technological inputs. Moreover, embeddedness within international networks of technological transactions enhances the entrepreneurial technological and economic performance.